Market Potential and Border Effects in Europe - Peter Huber; Michael Paffermayr; Yvonne Wolfmayr (European Regional Science Association (ERSA), 2006)
We estimate a linear approximation of the market potential function for Europe as derived in geography and trade models. Using a spatial econometric estimation approach, border effects are identified by a differential impact of nearby regions' purchasing power, depending on whether two regions are located within the EU15 or outside the EU15. Our results reveal substantial market potential effects on nominal wage rates. We also find significant border effects between EU15 and non-EU15 countries. Our estimation results suggest that the enlargement of the EU in May 2004 may lead to pronounced wage effects in the new member states, but to relatively small ones for the existing members and that regional disparities within new member states will increase.
Keywords: 330